The management and outcomes of patients with myelodysplastic syndrome with persistent severe thrombocytopenia: An observational single centre registry study. (January 2019) - Vijenthira, Abi; Premkumar, Devyani; Callum, Jeannie; Lin, Yulia; Wells, Richard A.; Chodirker, Lisa; Lenis, Martha; Mamedov, Alexandre; Buckstein, Rena
Highlights: Retrospective audit of a prospective national MDS registry study of 586 patients. 17% of patients had severe thrombocytopenia (<20 × 10 9 /L) lasting at least 8 weeks. Physicians used heterogeneous practices in prophylaxis against bleeding. 71% of patients on tranexamic acid or observation received no platelet transfusions. There was a low incidence of grade 3–4 bleeding (12%). Abstract: Background: Severe thrombocytopenia affects 10% of patients with myelodysplastic syndrome (MDS) and is associated with poor outcomes. The role for prophylactic platelet transfusions in the outpatient setting is unknown. Objective/methods: To audit treatments, bleeding rates, and transfusion requirements of patients with MDS and persistent severe thrombocytopenia (PST) registered in a prospective MDS registry at our center. Results: 99 (17%) of 586 total registry patients had PST; 28 were treated with tranexamic acid alone (TXA), 39 with TXA and prophylactic platelet transfusions (PROPH), 19 with PROPH alone, and 13 were untreated. Median duration of PST was 27 weeks and median overall survival was 0.9 years (95% CI 0.7–1.2). During the PST, 6% (6/99) of patients had a grade 4 bleeding event, from which 4 died. Platelet count at the time of grade 4 bleeding ranged from 2 to 19 × 10 9 /L. 66% (27/41) of patients on TXA alone or untreated required no therapeutic platelet transfusions and experienced no grade 3–4 bleeds. There were no significant differences in grade 3–4 bleeding rates between groups. Conclusions: Patients with MDS and PST had low rates of major bleeding but poor overall survival. Disparities in clinical practice likely relate to patient and provider heterogeneity and the lack of published evidence. The benefit of TXA and/or prophylactic platelet transfusions would be best evaluated by a randomized controlled trial.